Can carbon nanofibers affect anurofauna? Study involving neotropical Physalaemus cuvieri (Fitzinger, 1826) tadpoles - Batista Guimaraes, Abraao Tiago; Estrela, Fernanda Neves; Lima Rodrigues, Aline Sueli de; Nobrega, Rafael Henrique [UNESP]; Charlie-Silva, Ives; Malafaia, Guilherme (Elsevier B.V., 2021)
Although carbon nanotubes' (CNTs) toxicity in different experimental systems (in vivo and in vitro) is known, little is known about the toxic effects of carbon nanofibers (CNFs) on aquatic vertebrates. We herein investigated the potential impact of CNFs (1 and 10 mg/L) by using Physalaemus cuvieri tadpoles as experimental model. CNFs were able to induce nutritional deficit in animals after 48-h exposure to them, and this finding was inferred by reductions observed in body concentrations of total soluble carbohydrates, total proteins, and triglycerides. The increased production of hydrogen peroxide, reactive oxygen species and thiobarbituric acid reactive substances in tadpoles exposed to CNFs has suggested REDOX homeostasis change into oxidative stress. This process was correlated to the largest number of apoptotic and necrotic cells in the blood of these animals. On the other hand, the increased superoxide dismutase and catalase activity has suggested that the antioxidant system of animals exposed to CNFs was not enough to maintain REDOX balance. In addition, CNFs induced increase in acetylcholinesterase and butyrylcholinesterase activity, as well as changes in the number of neuromasts evaluated on body surface (which is indicative of the neurotoxic effect of nanomaterials on the assessed model system). To the best of our knowledge, this is the first report on the impact of CNFs on amphibians; therefore, it broadened our understanding about ecotoxicological risks associated with their dispersion in freshwater ecosystems and possible contribution to the decline in the populations of anurofauna species.
Keywords: Nanopollutants; Neurotoxicity; Cytotoxicity; REDOX imbalance; Uptake